Front Cover: Single Laser Shot Photoinduced Phase Transition of Rubidium Manganese Hexacyanoferrate Investigated by X‐ray Diffraction (Eur. J. Inorg. Chem. 27/2019). Issue 27 (17th June 2019) - Azzolina, Giovanni; Collet, Eric; Mariette, Céline; Cammarata, Marco; Trzop, Elzbieta; Sander, Mathias; Levantino, Matteo; Nakagawa, Kosuke; Tokoro, Hiroko; Ohkoshi, Shin‐ichi; Bertoni, Roman
Abstract : The Front Cover shows the ESRF synchrotron (bottom; image courtesy of ESRF/Pierre Jayet), where we studied the evolution of the crystal structure of the RbMnFe Prussian blue analogue (center) by X‐ray diffraction (rings at the top). We used a single laser shot for driving a phase transition in which photoinduced charge transfer, trapped by the structural reorganization, is responsible for the change in the magnetic properties of the system. This work was performed in the frame of the IM‐LED international laboratory (LIA, CNRS), JSPS, and ANR grants with a PhD funding from University Rennes 1. More information can be found in the Communication by E. Collet, R. Bertoni et al. For more on the story behind the cover research, see the Cover Profile .